Changes in lung function during an extreme mountain ultramarathon. Issue 4 (28th September 2014) - Vernillo, G.; Rinaldo, N.; Giorgi, A.; Esposito, F.; Trabucchi, P.; Millet, G. P.; Schena, F.
<x xml:space="preserve">Abstract</x> This study aimed to assess the effects of an extreme mountain ultramarathon (MUM, 330 km, 24 000 D+) on lung function. Twenty‐nine experienced male ultramarathon runners performed longitudinally [before (pre), during (mid), and immediately after (post) a MUM] a battery of pulmonary function tests. The tests included measurements of forced vital capacity, forced expiratory volume in 1 s, peak flow, inspiratory capacity, and maximum voluntary ventilation in 12 s (MVV12). A significant reduction in the running speed was observed (−43.0% between pre‐mid and mid‐post; P < 0.001). Expiratory function declined significantly at mid (P < 0.05) and at post (P < 0.05). A similar trend was observed for inspiratory function (P < 0.05). MVV12 declined at mid (P < 0.05) and further decreased at post (P < 0.05). Furthermore, there are significant negative correlations between performance time and MVV12 pre‐race (R = −0.54, P = 0.02) as well as changes in MVV12 between pre‐ and post‐race (R = −0.53, P = 0.009). It is concluded that during an extreme MUM, a continuous decline in pulmonary function was observed, likely attributable to the high levels of ventilation required during this MUM in a harsh mountainous environment.